2022
DOI: 10.1101/mcs.a006181
|View full text |Cite
|
Sign up to set email alerts
|

A Novel TP53 Tandem Duplication in a Child with Li-Fraumeni Syndrome

Abstract: Li-Fraumeni syndrome (LFS) is one of the most common cancer predisposition syndromes that affects both children and adults. Individuals with LFS are at an increased risk of developing various types of cancer over their lifetime including soft tissue sarcomas, osteosarcomas, breast cancer, leukemia, brain tumors, and adrenocortical carcinoma. Heterozygous germline pathogenic variants in the tumor suppressor gene TP53 are the known causal genetic defect for LFS. Single nucleotide variants (SNVs) including missen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Intragenic duplication plays an important role in the evolution, inheritance and variation of life, and involves gene expression, transcription regulation, chromosome construction and physiological metabolism ( Brahmachari et al, 1995 ; Saier Jr, 2016 ; Nava Rodrigues et al, 2019 ; Xu et al, 2022 ). For example, a recent study showed the crest phenotype in domestic chicken is caused by a 197 bp duplication in the intron of HOXC10 ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intragenic duplication plays an important role in the evolution, inheritance and variation of life, and involves gene expression, transcription regulation, chromosome construction and physiological metabolism ( Brahmachari et al, 1995 ; Saier Jr, 2016 ; Nava Rodrigues et al, 2019 ; Xu et al, 2022 ). For example, a recent study showed the crest phenotype in domestic chicken is caused by a 197 bp duplication in the intron of HOXC10 ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%